The practice of Canaanite cult: the Middle and Late Bronze ages - Susnow, Matthew (Ägypten und Altes Testament, 2021)
Intro -- Preface -- Content -- List of Abbreviations -- Part I: Introduction and Overview of the Research -- Chapter 1: Introduction -- 1.1 The Research Topic: Religion in the Southern Levant -- 1.2 The Need for a New Approach to Canaanite Religion -- 1.3 Aims and Research Questions -- 1.4 Methodology -- 1.5 The Novelty of this Book's Approach -- 1.6 Organizational Scheme of this Book -- Chapter 2: Overview of the Research: Working Definitions, Background, and Rationale -- 2.1 Definitions: Defining the Terms of this Study - "Middle and Late Bronze Canaan" and "Canaanite Religion" -- 2.2 General Overview of the MB and LB Southern Levant -- 2.3 History of Research and Scholarship of Canaanite Religion -- 2.4 Theory -- Part II: Cultic Architecture in the Southern Levant -- Chapter 3: Towards a New Direction in Analyzing Canaanite Cultic Architecture -- 3.1 What are Temples? -- 3.2 The Study of Cultic Architecture -- 3.3 The Layout of Part II -- Chapter 4: Architecture -- 4.1 Organization of the Analysis on Temple Architecture -- 4.2 The Intermediate Bronze Age -- 4.3 MB Open-Air Loci of Cultic Activity -- 4.4 Urban Migdal Temples in MB Canaan: A Standardized Form of Temple Architecture -- 4.4.1 Ugarit -- 4.4.2 Hazor -- 4.4.3 Megiddo -- 4.4.4 Shechem -- 4.4.5 Pella -- 4.4.6 Tel Haror -- 4.4.7 Tell el-Dab'a -- 4.5 Rural Migdal Temples -- 4.5.1 Tell el-Hayyat -- 4.5.2 Tel Kitan -- 4.6 Discussion: Migdal Temples in the Southern Levant and Beyond -- 4.7 Other less well-defined Temples from the MB -- 4.7.1 Givat Sharett -- 4.7.2 Naḥal Repha'im -- 4.7.3 Manaḥat -- 4.7.4 Al-Walajah -- 4.7.5 Ashkelon -- 4.8 New Temples in the LB -- 4.8.1 Lachish -- 4.8.2 Beth Shean -- 4.8.3 Tel Mevorakh -- 4.8.4 Hazor Area C -- 4.8.5 Tell Abu Hawam -- 4.8.6 Tell Abu Al-Kharaz -- 4.9 Discussion: Making Sense of the Diversity in Canaanite Temple Architecture.